2016
DOI: 10.1074/jbc.m115.675645
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Limits Adipocyte Hyperplasia through c-Myc Inhibition

Abstract: The expansion of fat mass in the obese state is due to increased adipocyte hypertrophy and hyperplasia. The molecular mechanism that drives adipocyte hyperplasia remains unknown. The NAD+-dependent protein deacetylase sirtuin 1 (SIRT1), a key regulator of mammalian metabolism, maintains proper metabolic functions in many tissues, counteracting obesity. Here we report that differentiated adipocytes are hyperplastic when SIRT1 is knocked down stably in mouse 3T3-L1 preadipocytes. This phenotype is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…Common genes identified by the different followed procedures were of special interest. Specifically, HSF1 , JARID2 , TCF4 and YBX3 play known roles in muscle development and protein metabolism [7074], while TFEB and MYC are involved in adipocyte proliferation, lipid metabolism and fatty acid transport [75, 76]. These TRF potentially regulate muscle and fat accretion in young pigs and are thus, of special interest in the understanding of molecular mechanisms underlying such processes in pigs and other species.…”
Section: Discussionmentioning
confidence: 99%
“…Common genes identified by the different followed procedures were of special interest. Specifically, HSF1 , JARID2 , TCF4 and YBX3 play known roles in muscle development and protein metabolism [7074], while TFEB and MYC are involved in adipocyte proliferation, lipid metabolism and fatty acid transport [75, 76]. These TRF potentially regulate muscle and fat accretion in young pigs and are thus, of special interest in the understanding of molecular mechanisms underlying such processes in pigs and other species.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adipocyte‐specific Nampt deletion also causes macrophage infiltration in adipose tissue , suggesting the important role of NAMPT‐NAD + ‐SIRT1 as a negative regulator of macrophage activation, a key feature that contributes to the development of obesity‐associated insulin resistance. Recently, it was also reported that SIRT1 inhibits adipocyte hyperplasia though the deacetylation of Lys323 on c‐Myc . Finally, it should be noted that SIRT1 enhances the enzymatic activity and secretion of eNAMPT by deacetylating Lys53 on NAMPT, thus affecting hypothalamic function and physical activity .…”
Section: Sirt1: a Key Molecular Link Between Nampt‐mediated Nad+ Biosmentioning
confidence: 98%
“…[ 122–125 ] High levels of SIRT1 were also observed in hyperplasia of adipocytes indicating its necessity in regulating adipose tissue function. [ 126 ] AMPK and SIRT modulate peroxisome proliferator‐activated receptor gamma coactivator 1α (PGC1α), a central factor regulating mitochondrial biogenesis and gene copy number thus modulating oxidative phosphorylation. [ 127,128 ] However, association of AMPK, SIRT, and mTOR dysfunction with metabolic disorder in aged tissues remains poorly understood.…”
Section: Dysfunctional Proteins Associated With Mitochondria In Metabmentioning
confidence: 99%